In vitro pharmacological profiling of R406 identifies molecular targets underlying the clinical effects of fostamatinib. Issue 5 (4th September 2015) - Rolf, Michael G.; Curwen, Jon O.; Veldman‐Jones, Margaret; Eberlein, Cath; Wang, Jianyan; Harmer, Alex; Hellawell, Caroline J.; Braddock, Martin
Abstract: Off‐target pharmacology may contribute to both adverse and beneficial effects of a new drug. In vitro pharmacological profiling is often applied early in drug discovery; there are fewer reports addressing the relevance of broad profiles to clinical adverse effects. Here, we have characterized the pharmacological profile of the active metabolite of fostamatinib, R406, linking an understanding of drug selectivity to the increase in blood pressure observed in clinical studies. R406 was profiled in a broad range of in vitro assays to generate a comprehensive pharmacological profile and key targets were further investigated using functional and cellular assay systems. A combination of traditional literature searches and text‐mining approaches established potential mechanistic links between the profile of R406 and clinical side effects. R406 was selective outside the kinase domain, with only antagonist activity at the adenosine A3 receptor in the range relevant to clinical effects. R406 was less selective in the kinase domain, having activity at many protein kinases at therapeutically relevant concentrations when tested in multiple in vitro systems. Systematic literature analyses identified KDR as the probable target underlying the blood pressure increase observed in patients. While the in vitro pharmacological profile of R406 suggests a lack of selectivity among kinases, a combination of classical searching and text‐mining approaches rationalized the complex profile establishing linkage between off‐target pharmacology and clinically observed effects. These results demonstrate the utility of in vitro pharmacological profiling for a compound in late‐stage clinical development.